In Peritoneal Dialysis, Is There Sufficient Evidence to Make “PD First” Therapy? - Pranav Dalal; Harbaksh Sangha; Kunal Chaudhary (International Journal of Nephrology)
Since its introduction more than 3 decades ago, the use of peritoneal dialysis (PD) has increased greatly due to its simplicity, convenience, and low cost. Advances in technique, antibiotic prophylaxis, and the introduction of newer solutions have improved survival, quality of life, and reduced rate of complications with PD. In Hong Kong, approximately 80% end-stage renal disease (ESRD) patients perform PD; in others, that is, Canada, Australia, and New Zealand, 20%–30% patients use PD. However, in the United States, the annual rate of prevalent patients receiving PD has reduced to 8% from its peak of 15% in mid-1980s. PD as the initial modality is being offered to far less patients than hemodialysis (HD), resulting in the current annual incidence rate of less than 10% in USA. There are many reasons preventing the PD first initiative including the increased numbers of in-center hemodialysis units, physician comfort with the modality, perceived superiority of HD, risk of peritonitis, achieving adequate clearances, and reimbursement incentives to providers. Patient fatigue, membrane failure, and catheter problems are other reasons which discourage PD utilization. In this paper, we discuss the available evidence and provide rationale to support PD as the initial renal replacement modality for ESRD patients.